As espacialidades do viver-morrer no ciclo utópico-distópico da série literária O doador de memórias - Persicano, Léa Evangelista (2023)
This doctoral thesis is located in the area of Literary Studies, it is aligned with the representation of space in fantastic narratives and its main objective is to understand how the architectonics of spaces is inseparable from collective and individual perceptions about life and death and is articulated to utopian and/or dystopian ideals leading to the objectification/(dis)subjectification of individuals and subjects inserted in it. The object of study is the literary series O doador de memórias (2014-2016), by the American author Lois Lowry (1937), composed of four books: O doador de memórias (2014a), A escolhida (2014b), O Mensageiro (2016a) and O filho (2014c), translated from English into Portuguese. The angle of analysis adopted are the spatialities of living and dying in three different scenarios: the village-city of the gray color, the village behind the ruin and the colorful village of diversity, socioculturally very different, located on the same geographical map, interconnected by forests and rivers traversed in the migratory flows of the character-subjects and by apparently very different governmental ideals. As a main theoretical reference, authors and researchers such as Michel Foucault, Giorgio Agamben, Marisa Martins Gama-Khalil, Nilton Milanez, Gaston Bachelard, Jean-Luc Nancy, Gregory Claeys, Alexander Meireles da Silva, Plato, Michel Lauwers, Philippe Ariès, Norbert Elias, Emmanuel Levinas are mobilized. They are used to think about knowledge-power relations, disciplinary and control devices, the processes of objectification/(dis)subjectification of subjects, issues related to space and the body, the characteristics of utopia and dystopia, and the theme of death and life. The thesis has five chapters and, in the contexture of the four analytical-theoretical chapters, the narrative perspectives associated with the gaze of the central characters, chosen by the local governments because of their magical talents endowed with power and capable of controlling the future of the population, emerge.